Optimizing the breadth of SARS-CoV-2-neutralizing antibodies in vivo and in silico - Kuroda, Daisuke; Moriyama, Saya; Sasaki, Hiroaki; Takahashi, Yoshimasa (Human vaccines & immunotherapeutics, 2025)
Since the emergence of SARS-CoV-2, the ongoing arms race between mutating viruses and human antibodies has revealed several novel strategies by which antibodies adapt to viral escape. While SARS-CoV-2 viruses exhibit high variability in epitopes targeted by neutralizing antibodies, certain epitopes remain conserved owing to their essential roles on viral fitness. Antibodies can acquire broadly neutralizing activity by targeting these vulnerable sites through affinity-based somatic evolution of immunoglobulin genes. Notably, the specificity encoded in antibody germline genes also plays a fundamental role in acquiring the breadth. In-depth genetic and structural analyses of the antibody repertoires have uncovered multiple strategies for adapting to evolving targets. The integration of large-scale antibody datasets with computational approaches increases the feasibility and efficiency of designing broadly neutralizing antibody therapeutics from ancestral antibody clones with limited initial efficacy. In this review, we discuss strategies to optimize antibody breadth for the development of broadly neutralizing antibody therapeutics and vaccine antigens.